2009
DOI: 10.1017/s0954422409990023
|View full text |Cite
|
Sign up to set email alerts
|

Stroke: roles of B vitamins, homocysteine and antioxidants

Abstract: In the present review concerning stroke, we evaluate the roles of B vitamins, homocysteine and antioxidant vitamins. Stroke is a leading cause of death in developed countries. However, current therapeutic strategies for stroke have been largely unsuccessful. Several studies have reported important benefits on reducing the risk of stroke and improving the post-stroke-associated functional declines in patients who ate foods rich in micronutrients, including B vitamins and antioxidant vitamins E and C. Folic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 169 publications
(173 reference statements)
3
53
1
Order By: Relevance
“…Small but useful, they conclude, and worthy of further investigation as adjunctive therapy alongside fibrinates or statins. Vitamins have also been implicated as being protective against CVD, in particular folate and the B vitamins, via their plasma homocysteine-lowering effect, as reported here by Sánchez-Moreno et al (4) in the context of stroke. Whether this effect will track through to an actual reduction of stroke risk among patients with hyperhomocysteinaemia will not be clear until the conclusion of several ongoing intervention studies.…”
supporting
confidence: 70%
“…Small but useful, they conclude, and worthy of further investigation as adjunctive therapy alongside fibrinates or statins. Vitamins have also been implicated as being protective against CVD, in particular folate and the B vitamins, via their plasma homocysteine-lowering effect, as reported here by Sánchez-Moreno et al (4) in the context of stroke. Whether this effect will track through to an actual reduction of stroke risk among patients with hyperhomocysteinaemia will not be clear until the conclusion of several ongoing intervention studies.…”
supporting
confidence: 70%
“…This includes 50% of total fat intake and 48% of fibre intake; increased intake of both total fat and fibre has been implicated as a risk factor for the development of cancer (WCRF, 2007). Important micronutrient intakes (Chakraborti et al, 2002;Voutilainen et al, 2006;WCRF, 2007;Sanchez-Moureno et al, 2009). The associations with nutrient intake are similar to the results we reported in the women's study .…”
Section: Dietary Patterns In Men K Northstone and Pm Emmettmentioning
confidence: 99%
“…Under normal conditions, the endogenous and exogenous antioxidants scavenge free radicals and inhibit the harmful effects of oxidative stress [8]. Previous investigations revealed that after IBI, the concentrations of glutathione and ascorbic acid (AA) are decreased, while free radicals are increased [9,10], suggesting that increasing the concentration of AA, which may act as an antioxidant under these conditions, could be considered as new therapeutic strategy for treatment of IBI [11].One vitamer form of AA, vitamin C, is a potential antioxidant factor that can neutralize free radicals (especially hydroxyl radicals) via electron transfer, especially in brain parenchyma [12,13]. It has been shown that antioxidant treatment with AA significantly reduces lipid peroxidation and increases superoxide dismutase and catalase activities after seizures induced by pilocarpine [14].…”
mentioning
confidence: 99%
“…Under normal conditions, the endogenous and exogenous antioxidants scavenge free radicals and inhibit the harmful effects of oxidative stress [8]. Previous investigations revealed that after IBI, the concentrations of glutathione and ascorbic acid (AA) are decreased, while free radicals are increased [9,10], suggesting that increasing the concentration of AA, which may act as an antioxidant under these conditions, could be considered as new therapeutic strategy for treatment of IBI [11].…”
mentioning
confidence: 99%